Viral Invasion of the Oral Cavity: A Review of Viral Impact on Oral Health and the Potential Use of Saliva as a Diagnostic Tool - Senthilraj Rajapandi; Evelyn Sharon Sukumaran; Keerthanashree Reddy Napa Prasad; Anushya Vardhini Venkatesan; Tamil Azhagan Shanmugavel Ravichandran; Sarvesh Sabarathinam (Frontiers in Bioscience-Elite)
The oral cavity is a complex ecosystem that harbors a diverse microbial community. Viral infections can significantly disrupt this delicate balance, leading to various oral health issues. This review delves into the intricate relationship between viruses and oral health, exploring the impact of both RNA and DNA viruses. We discuss the mechanisms through which these viruses influence the oral microbiome, modulate immune responses, and contribute to various oral diseases, including periodontal disease, oral candidiasis, and oral cancer. Additionally, we highlight the potential of saliva as a valuable diagnostic tool for viral infections and oral health assessment. By understanding the viral–oral health nexus, we can develop effective strategies for prevention, early diagnosis, and targeted interventions to improve oral health outcomes.